2023
DOI: 10.1039/d3cp01009k
|View full text |Cite
|
Sign up to set email alerts
|

Alkylphosphonium carboxylate ionic liquids with tuned microscopic structures and properties

Abstract: Eleven pure alkylphosphonium carboxylate ionic liquids were synthesised following a reliable and accessible route. Tetrabutylphosphonium and tetradecyltrihexylphosphonium cations were associated to a variety of [R COO]– anions with R varying...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 76 publications
2
19
0
Order By: Relevance
“…Thus, σ has been scaled by a factor 0.95 in order to correct the systematic underestimation of densities while keeping the constancy and transferability of the model. 23 The distance between the centers of mass of the fragments, the geometric parameters, the atomic partial charges of molecules and ions, as well as the dipole moments of fragments were taken taken either from the CL&Pol force field 28 or from a previous study in which the missing parameters for the phosphonium carboxylate ILs under study were determined. 23 Only the distance between the centers of mass of CO 2 and SO 2 and the various fragments of [P 4,4,4,4 ][TetrazC 1 COO] have been calculated through a geometry optimization using dispersion-corrected density functional theory (DFT-D3) 34 at the B97-D3/cc-pVDZ level (Table S8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, σ has been scaled by a factor 0.95 in order to correct the systematic underestimation of densities while keeping the constancy and transferability of the model. 23 The distance between the centers of mass of the fragments, the geometric parameters, the atomic partial charges of molecules and ions, as well as the dipole moments of fragments were taken taken either from the CL&Pol force field 28 or from a previous study in which the missing parameters for the phosphonium carboxylate ILs under study were determined. 23 Only the distance between the centers of mass of CO 2 and SO 2 and the various fragments of [P 4,4,4,4 ][TetrazC 1 COO] have been calculated through a geometry optimization using dispersion-corrected density functional theory (DFT-D3) 34 at the B97-D3/cc-pVDZ level (Table S8).…”
Section: Methodsmentioning
confidence: 99%
“…This observation seems to contradict the expected deshielding effect of hydrogen bonds on protons but can be explained by the solvation of SO 2 around the O COO − site that decreases the interaction between the negatively charged headgroup of the anion and the H α of the cation. 23 The signals related to the anion are shifted downfield, indicating a decrease in electron density, likely due to the electrophilic nature of the sulfur atoms interacting with the carboxylate anion.…”
mentioning
confidence: 99%
“…The stability of these aggregates was explained by the interactions of the counterions, located at the periphery of the cation clusters. More recently Scaglione et al [4] have also reported evidence of anion-anion interactions in one phosphonium tetrazolate IL with unique physical-chemical properties using molecular dynamics simulation and small angle X-ray scattering. In the case, it is the delocalization of the charge in the tetrazole ring of the anion that allows for an unexpected proximity of the anions in the liquid salt.Tetracyanoborate ions [B(CN)4] − are known to form ILs with low density and low viscosity, [5] with relatively high electrical conductivity [6] and capable of dissolving large quantities of CO2.…”
mentioning
confidence: 99%
“…More recently Scaglione et al 4 have also reported evidence of anion−anion interactions in one phosphonium tetrazolate IL with unique physical−chemical properties using molecular dynamics (MD) simulation and small-angle X-ray scattering (SAXS). In this case, it is the delocalization of the charge in the tetrazole ring of the anion that allows for an unexpected proximity of the anions in the liquid salt.…”
mentioning
confidence: 99%
“…More recently Scaglione et al . have also reported evidence of anion–anion interactions in one phosphonium tetrazolate IL with unique physical–chemical properties using molecular dynamics (MD) simulation and small-angle X-ray scattering (SAXS).…”
mentioning
confidence: 99%